Role of Energy Efficiency and Conservation Including Demand Side Management for Sustainable Development in India - Kumar, Rakesh; Ranjan, Rakesh; Chandra Verma, Mukesh (International Journal of Engineering and Technology, 2018)
Energy is used to provide cost-effective services meet the objectives of promoting sustainable development. The importance of Energy Efficiency and Conservation (EE and EC) is to conserve depleting energy resources. Energy efficiency in India has been increasing which has led the Government of India through the Energy Conservation Act (ECA) and the Bureau of Energy Efficiency (BEE) to begin several programs. Demand Side Management (DSM) and Energy Efficiency and Conservation are improving the economic growth of Indian utilities.DSM also aimed at promoting the installation and use of energy efficient equipment that consume less power having good quality of output. Energy efficiency is important for sustainable future. Demand Side Management including Demand Response (DR) Activity is utilized to limit the peak electricity demand. DSM helps grid operators to act as virtual power plants and power the utilities to transmit energy when needed through demand response measures. Demand Response (DR) measures can be adapted for a industrial and commercial facility that includes turning off air conditioning, lighting, pumps, and other non-essential equipment. Demand Response is a Demand Side Management (DSM) method in which the end users of electricity are encouraged to take part in dropping the peak load on the system by altering their normal energy consumption schedule. The basic objective of the Agriculture, Municipal and Industrial Demand Side Management (DSM) programmes are to improve the overall energy efficiency of the SLDC (State Load Dispatch Centre) and Electricity Grids which could lead to substantial savings in the electricity consumption, resulting in cost reduction and savings. The target of energy saving can be achieved by implementing acts and policies which leads to state wise DSM Regulations by Regulatory Commissions to the State Power Utilities. The Role of DSM and Energy Efficiency including conservation can fulfill the dreams projects electricity demand in Smart Cities. The Role of State Electricity Regulatory Commissions and Forum of Regulators are very important to make Indiaâ€™s electricity demand in future.Â Â